2016
DOI: 10.1103/physrevb.93.064507
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity at 9 K inMo5PB2with evidence for multiple gaps

Abstract: Superconductivity is observed with critical temperatures near 9 K in the tetragonal compound Mo5PB2. This material adopts the Cr5B3 structure type common to supercondcuting Nb5Si3−xBx, Mo5SiB2, and W5SiB2, which have critical temperatures of 5.8−7.8 K. We have synthesized polycrystalline samples of the compound, made measurements of electrical resistivity, magnetic susceptibility, and heat capacity, and performed first principles electronic structure calculations. The highest Tc value (9.2 K) occurs in slightl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 43 publications
6
26
0
1
Order By: Relevance
“…22,29 T2 phases have an M 5 AB 2 composition in an I4/mcm space group symmetry, where M is a transition metal from Groups 5 to 9, and A is an Aelement (Si, Ge, and P). T2 phases are attractive due to their high oxidation resistance, 30 nearly isotropic thermal expansion, 31 superconducting properties 32,33 and potential for use as rare-earth free permanent magnets. [34][35][36] We have recently shown that metal alloying in Si-based T2 phases holds potential for a range of new compositions, including the discovered out-of-plane ordered Ti 4 MoSiB 2 , called o-MAB.…”
Section: Introductionmentioning
confidence: 99%
“…22,29 T2 phases have an M 5 AB 2 composition in an I4/mcm space group symmetry, where M is a transition metal from Groups 5 to 9, and A is an Aelement (Si, Ge, and P). T2 phases are attractive due to their high oxidation resistance, 30 nearly isotropic thermal expansion, 31 superconducting properties 32,33 and potential for use as rare-earth free permanent magnets. [34][35][36] We have recently shown that metal alloying in Si-based T2 phases holds potential for a range of new compositions, including the discovered out-of-plane ordered Ti 4 MoSiB 2 , called o-MAB.…”
Section: Introductionmentioning
confidence: 99%
“…One of the interesting subsets of these compounds is the ternary borides with stoichiometries M 5 XB 2 (where X = P, Si). These systems exhibit many interesting electronic ground states [2]. It has been reported that these ternary borides are formed with many transition metals including the 3d transition metals from V to Co, the 4d transition metals Nb and Mo, and the 5d transition metal W [2].…”
Section: Introductionmentioning
confidence: 99%
“…These systems exhibit many interesting electronic ground states [2]. It has been reported that these ternary borides are formed with many transition metals including the 3d transition metals from V to Co, the 4d transition metals Nb and Mo, and the 5d transition metal W [2]. For instance, Mn 5 SiB 2 shows ferromagnetic behavior with Curie temperature at room temperature [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Впоследствии оказалось, что MgB2 -не единственный сверхпроводник с двумя зонами и соответственно с двумя щелевыми особенностями. Свидетельства двухщелевой сверхпроводимости были обнаружены даже в таком достаточно тривиальном сверхпроводнике как свинец [3], а кроме того, в сплавах молибдена с рением [4], сложных соединениях Mo5PB2 [5], Mo8Ga41 [6] и RuB2 [7]. Основным доказательством наличия двух энергетических щелей являются эксперименты по измерению дифференциальной проводимости G(V) = dI(V)/dV гетероструктуры, образованной металлическим инжектором и сверхпроводником (S), которые образуют либо непосредственный контакт (контактная спектроскопия), либо разделены наноразмерной пленкой изолятора (I), сквозь которую электроны туннелируют согласно законам квантовой механики.…”
Section: Introductionunclassified